2022
DOI: 10.1186/s12954-022-00588-7
|View full text |Cite
|
Sign up to set email alerts
|

“It’s called overamping”: experiences of overdose among people who use methamphetamine

Abstract: Background The USA is experiencing increases in methamphetamine use and methamphetamine-related or attributed deaths. In the current study, we explore qualitative narratives of methamphetamine overdose and strategies used by people who use drugs to reduce the undesirable effects associated with methamphetamine use. Methods We conducted 21 qualitative interviews with people over the age of 18 who reported using methamphetamine in the previous 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Experiences with overamping, isolation, and withdrawal mirror the current literature describing the negative consequences of use, 32 but participants also explored how methamphetamine can enhance function and strengthen relationships. This “moving” line between methamphetamine’s risks and benefits highlights the need for nuanced conversations about substance use in medical settings.…”
Section: Discussionmentioning
confidence: 96%
“…Experiences with overamping, isolation, and withdrawal mirror the current literature describing the negative consequences of use, 32 but participants also explored how methamphetamine can enhance function and strengthen relationships. This “moving” line between methamphetamine’s risks and benefits highlights the need for nuanced conversations about substance use in medical settings.…”
Section: Discussionmentioning
confidence: 96%
“…It has previously been reported that using methamphetamines, heroin or a combination of opioids and stimulants are associated with increased risk of death. Excess mortality among methamphetamine/heroin users may be due to suicide or unintentional drug overdose or long-term medical conditions [ 40 ]. According to the World Health Organization (WHO), globally, 600,000 deaths were attributable to drug overdose in 2019, with approximately one quarter of those deaths caused by semisynthetic opioid overdose [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), globally, 600,000 deaths were attributable to drug overdose in 2019, with approximately one quarter of those deaths caused by semisynthetic opioid overdose [ 41 ]. However, differentiating unintentional acute drug toxicity from intentional substance-related deaths is not easy in most cases, particularly in methamphetamine-related deaths [ 40 ]. Although the presence of suicidal thoughts among illicit substance users is a significant risk factor for future suicide attempts and deaths, non-substance-related methods of self-killing, such as hanging or death by firearms, are more frequent methods for suicide deaths among this population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be that changes in methamphetamine composition could also underlie some of the experiences described in this study. Specifically, methamphetamine containing d -methamphetamine salts without l -methamphetamine salts, which can be removed during some manufacturing processes ( 29 ), has been associated with stronger and shorter duration effects, a “sleepy” effect (sometimes described as “shutting down”) after using methamphetamine ( 22 ), and more psychiatric symptoms such as delusions and paranoia ( 30 ), some of which were described by our respondents as undesirable effects they sought to mitigate.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the current study were collected as part of a larger sequential mixed-methods study ( 22 ). Between December 2019 and February 2020, we recruited people who use methamphetamine in Reno, Nevada and Rio Arriba County, New Mexico.…”
Section: Methodsmentioning
confidence: 99%